Malignancy Risk Factors of Hydatidiform Mole: Faktor-Faktor Risiko Keganasan pada Molahidatidosa - Akbar N D Saputra; Agustria Z Shaleh; Patiyus Agustiansyah; Theodorus Theodorus (Indonesian Socety of Obstetrics and Gynecology, 2019)
Abstract Objective: to determine risk factors inhydatidiform mole patients who will develop into Gestational Trophoblast Neoplasm (GTN) in Dr.Mohammad Hoesin Hospital Palembang Method: An observational analytical study with case control design was conducted in Department of Obstetrics and Gynecology in Dr. Mohammad Hoesin Hospital Palembang / Faculty of Medicine Sriwijaya University Palembang from January 2017 to August 2017. The frequency and distribution of data are described in tables. Bivariate analysis was done to determine correlation between independent variable and dependent variable using Chi Square/Fisher Exact test and multivariate analysis was used to know which independent variable has the biggest influence to the occurrence of Gestational TrophoblastNeoplasm (GTN) post evacuation of hydatidiform mole. Data analysis was done using SPSS version 21.0. Results: There were 45 patients who fulfilled inclusion criteria with control group and case group ratio 1 : 2 (15 cases and 30 controls). Statistical analysis showed a significant correlation between patient age, pre-evacuation Î² HCG level, parity, and histopathologic appearance with occurrence of Gestational Trophoblast Neoplasm (GTN) after evacuation of hydatidiform mole (p <0,05). From multivariate analysis, it was found that pre-evacuation Î² HCG levels â‰¥ 134,182.5 mIU/ml was a risk factor of Gestational Trophoblast Neoplasm (OR = 77.008, p value = 0.004). Conclusion: Pre-evacuation Î² HCG levels â‰¥ 134,182.5 mIU / ml is a risk factor for the occurrence of Gestational Trophoblast Neoplasm (GTN). Keywords: Hydatidiform mole, GTN, age, pre-evacuation Î² HCG level, parity, uterine size, blood type, hysthopathology feature